Ecology of Marine Bivalves An Ecosystem Approach - Dame, Richard F. (Taylor & Francis, 2011)
Bivalves, such as clams and oysters, are species having two-valved shells. In the marine ecosystem these species play a unique and essential role. This book examines the ecology of bivalves from an ecosystem or holistic view, taking into consideration their processes, interactions, and components. Studies of bivalves at the physical, organismic, and population levels are presented as foundations for understanding ecosystem processes. Ecology of Marine Bivalves: An Ecosystem Approach explores the potential use of bivalves as indicators and monitors of ecosystem health and describes experiments from the perspective of computer simulations, mesocosm studies, and field manipulation experiments. The theories of many areas of science support the various approaches. Concise reviews and more than 70 tables and figures give you rapid access to synthesized data about these keystone species.